Corporate Culture, Societal Culture, and Institutions - Guiso, Luigi; Sapienza, Paola; Zingales, Luigi (American Economic Review, 2015)
While both cultural and legal norms (institutions) help foster cooperation, culture is the more primitive of the two and itself sustains formal institutions. Cultural changes are rarer and slower than changes in legal institutions, which makes it difficult to identify the role played by culture. Cultural changes and their effects are easier to identify in simpler, more controlled, environments, such as corporations. Corporate culture, thus, is not only interesting per se, but also as a laboratory to study the role of societal culture and the way it can be changed.